Vulnerability to surface water contamination of Pirapó River Basin, Paraná - Graça, Carlos Henrique da; Silveira, Hélio (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2020)
Water is one of the most important resources for the survival of living beings, and must be very well managed, so as not to compromise the quality of life of future generations. One of the biggest challenges is to reduce the effects of water deficiency and contamination. The objective of this work is to establish a classification of the vulnerability to the contamination of surface waters, aiming to contribute with the more effective management of the hydrographic basin of the Pirapó - Paraná River. For this, a semi-empirical model of Morgan, Morgan and Fenney (MMF - modified) was applied. The results show that vulnerability to surface water contamination showed a higher percentage linked to the average vulnerability, corresponding to approximately 63% of the basin area. This classification is related to the occurrence of deep soils (Oxisols and Nitosols) and resistant to the release of particles, with lower values ​​of surface runoff influenced by the reduction in the intensity of precipitation, in addition to being over moderate slope areas, with a predominance of classes between 6 and 15%. Thus, it is considered that the study may contribute to the development of more favorable actions for the protection of surface waters in the basin, prioritizing specific areas of protection for the monitoring of its waters.